Strength analysis of cold-rolled steel roof truss members consist of hat channel and c-channel with different thickness - Nurhafizah , Nashruddin (2012)
A roof truss is a very important structure when constructing the roof. It transfers the dead load and the live load from the roof to the nearest structural support such as column. The strength test on the truss member is a very essential procedure as it will determine whether the member type is suitable to sustain the load or not. It can also help in determining the most economical material to be used in the construction hence cutting the construction cost. Laboratory test provides more accurate results because it is tested directly onto the material but it must be done according to the related standard specification. This research's purpose is to determine the maximum tensile strength the available cold-rolled steel channel can afford before it counters failure. This test was carried out by the Universal Testing Machine (20kn-5OkN) for the coupon test and 3-point load Bending Testing Machine for the bending test.